Application of a collocation method based on linear barycentric interpolation for solving 2D and 3D Klein-Gordon-Schrödinger (KGS) equations numerically. Issue 5 (2nd December 2020) - Oruç, Ömer
Abstract : Purpose: The purpose of this paper is to obtain accurate numerical solutions of two-dimensional (2-D) and 3-dimensional (3-D) Klein–Gordon–Schrödinger (KGS) equations. Design/methodology/approach: The use of linear barycentric interpolation differentiation matrices facilitates the computation of numerical solutions both in 2-D and 3-D space within reasonable central processing unit times. Findings: Numerical simulations corroborate the efficiency and accuracy of the proposed method. Originality/value: Linear barycentric interpolation method is applied to 2-D and 3-D KGS equations for the first time, and good results are obtained.